Hydrodynamic Constraints on Ore Formation by Basin‐Scale Fluid Flow at Continental Margins: Modelling Zn Metallogenesis in the Devonian Selwyn Basin - Alejandro Rodríguez; Philipp Weis; Joseph M. Magnall; Sarah A. Gleeson (Geochemistry, Geophysics, Geosystems, 2021)
Abstract The clastic‐dominant (CD‐type) deposits that are contained within sedimentary basins are major resources of Zn, Pb and Ag, but their formation by basin‐scale hydrothermal mass and energy transport processes is still poorly understood. Using geological constraints from the Late Devonian Selwyn Basin (Canada), we apply quantitative numerical fluid flow modeling to explore the effect of strata permeability, timing of fault opening and increased heat flow in controlling fluid migration, metal leaching and ore formation during an extensional tectonic event. The results indicate that tapping hot fluids from a confined and permeable aquifer at several km depths by means of permeable normal faults is a key factor for the formation of large Zn‐Pb deposits. The hot (282°C) ore‐forming fluids are transported to the shallow subsurface shortly after the initiation of a rifting event (within 100 kyr), before the development of extensive basin‐scale convection patterns that lead to stronger cooling and a reduction in the capacity of the hydrothermal system to make an economic deposit. Such a hydrothermal event can result in metal endowments comparable to the deposits of the Selwyn Basin.